Projeto Inova Sobral : percepção dos gestores de uma política pública de apoio à inovação - Rodrigues, Francisca América Fernandes (My University, 2022)
The corporate environment and public policies are concerned with young people's paths in their professional lives. In the current innovation and technological revolution scenario, startups emerge as relevant actors and one of the primary sources of innovation as an incentive for entrepreneurship.The objective of this study was to identify how the Inova Sobral Project contributes to strengthening public policy to support innovation in the perception of managers. As for the methodological aspects, applied descriptive and exploratory character research with a qualitative approach was adopted. Data collection was carried out with 12 interviewees, representatives of the Municipality of Sobral, Higher Education Institutions, SENAI, and SEBRAE. The results made it possible to identify and highlight that the Inova Sobral Project is critical in the regional scenario, mainly in encouraging technological innovation through technical, methodological, and structural support. The project fulfilled the goal of creating 10 startups and the public space favorable to the emergence of entrepreneurial ideas to carry out the actions. They highlighted the importance of integration between work fronts, universities, institutions, and government to promote the development of technological actions through innovative projects. Furthermore, it was identified that the occurrence of failures in the planning of the stages, lack of monitoring in the execution stages, and interaction between the managers. [resumo fornecido pelo autor]
O meio corporativo e as políticas públicas preocupam-se com os caminhos que os jovens podem seguir na vida profissional. No cenário atual de inovação e revolução tecnológica, as startups surgem como atores relevantes e uma das principais fontes de inovação como incentivo ao empreendedorismo. O objetivo desse estudo foi identificar como o Projeto Inova Sobral contribui para o fortalecimento da política pública de apoio a inovação na percepção dos gestores. Quanto aos aspectos metodológicos, adotou-se uma pesquisa aplicada de caráter descritivo e exploratório com abordagem qualitativa. A coleta de dados foi realizada com 12 entrevistados, representantes da Prefeitura de Sobral, Instituições de Ensino Superior, SENAI e SEBRAE. Os resultados permitiram identificar e destacar que o Projeto Inova Sobral é importante para fortalecer o ecossistema de inovação no cenário regional, principalmente, no incentivo inovação tecnológica através de apoio técnico, metodológico e estrutural. O projeto cumpriu a meta da criação de 10 startups e o espaço público favorável ao surgimento de ideias empreendedoras para realização das ações. Destacaram a importância da integração entre frentes de trabalho, universidades, instituições e governo para promoverem o desenvolvimento das ações tecnológicas através dos projetos inovadores. Ademais, identificou-se a ocorrência de falhas no planejamento das etapas, ausência de acompanhamento nas fases de execução e interação entre os gestores. [resumo fornecido pelo autor]
Keywords: Empreendedorismo; Administração; Política pública; Empresas novas; Entrepreneurship; Management; Public policy; New business enterprises